Chlorhexidine mouthrinse in combination with an LScontaining dentifrice and a dentifrice slurry - D. A. C. Van Strydonck (journal of clinical periodontology, 2006)
Objectives: The aim of the present study was to compare the plaque-inhibitory effect of a 0.2% chlorhexidine digluconate (CHX) rinse when preceded by ordinary toothbrushing with a 1.5% sodium lauryl sulphate (SLS)-containing dentifrice to the effect of the same rinse when used alone, or when preceded by rinsing with an SLS-containing slurry. Methods: The study was an examiner blinded, randomized three-arm, parallel design. It used a 4-day plaque accumulation model to compare three different oral hygiene regimens, which were performed under supervision. One hundred and twenty healthy volunteers were enrolled in the study and were randomly assigned to one of each group. At the beginning of each test period, they received a thorough dental prophylaxis. The experiment was performed in one randomly assigned (upper or lower) jaw, called the study jaw. The opposite jaw, referred to as the dentifrice jaw, served only to introduce the influence of toothbrushing with a dentifrice on the antiplaque efficacy of the CHX in the study jaw of the same mouth. At the end of the 4-day test period, plaque and gingival bleeding were scored in the study jaw. In all the regimens, the oral hygiene procedure was finalized by rinsing with a CHX 0.2% solution for 1 min. The study jaw was not brushed during the experiment. Regimen A (positive control) consisted of rinsing with CHX alone. In regimen B, rinsing with CHX was preceded by rinsing with an SLS-containing slurry, while in regimen C rinsing with CHX was preceded by toothbrushing with an SLS-containing dentifrice in the dentifrice jaw. No other oral hygiene measures were allowed. After 4 days of undisturbed plaque accumulation, the amount of plaque and level of gingival health were evaluated. Results: The overall plaque index for regimens A, B and C was 1.17, 1.62, and 1.14, respectively. There was no significant difference in plaque accumulation between the CHX alone regimen (A) and the SLS–dentifrice–CHX regimen (C). Regimen B differed significantly from regimens A and C. The overall bleeding index for regimens A, B and C was 0.24, 0.18, and 0.20, respectively. There was no significant difference between the three regimens. Conclusions: The present study shows that the anti-plaque efficacy of a 0.2% CHX rinse was not reduced when preceded by everyday toothbrushing with a SLScontaining dentifrice. However, when preceded by rinsing with an SLS-containing slurry, the anti-plaque efficacy of a 0.2% CHX rinse was reduced.